2002
DOI: 10.1017/s0022029902005447
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of ewe milk as affected by solar radiation and high ambient temperature

Abstract: Forty lactating Comisana ewes were either exposed to or protected from solar radiation and fed either in the morning or afternoon during summer in a Mediterranean climate. Individual milk samples were taken on days 7, 21 and 42 of the study period to determine fatty acid composition by gas chromatography. Exposure to solar radiation resulted in higher proportions of short-chain and saturated fatty acids in milk, primarily because of increased contents of caproic, capric, lauric, myristic and stearic acids (by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Within SAFA, palmitic acid (C16:0), myristic acid (C14:0) and stearic acid (C18: 0) accounted for the highest proportions in milk fat of both breed species with mean values 44.11% for goat and 46.26% for ewes correspondingly. Similar results were reported by Tomotake et al (2006); Bernard et al (2005); Sevi et al (2002) and Atti et al (2006) for Silico-Sarde, Comisana ewes and Alpine and JapaneseSaanen goats fed on different diets.…”
Section: Resultssupporting
confidence: 88%
“…Within SAFA, palmitic acid (C16:0), myristic acid (C14:0) and stearic acid (C18: 0) accounted for the highest proportions in milk fat of both breed species with mean values 44.11% for goat and 46.26% for ewes correspondingly. Similar results were reported by Tomotake et al (2006); Bernard et al (2005); Sevi et al (2002) and Atti et al (2006) for Silico-Sarde, Comisana ewes and Alpine and JapaneseSaanen goats fed on different diets.…”
Section: Resultssupporting
confidence: 88%
“…Circulating glucose concentrations were increased in pigs (Prunier et al 1997) and cattle (Denbow et al 1986), but decreased in sheep (Achmadi et al 1993) and cattle (Shwartz et al 2009;Wheelock et al 2010), and unchanged in pigs in another study (de Bragança and Prunier 1999) under hot conditions. Heat exposure increased plasma NEFA in sheep (Sevi et al 2002), but decreased NEFA in lactating cattle (Itoh et al 1998;Shwartz et al 2009;Wheelock et al 2010). These differences between basal hormone and metabolite concentrations may relate to differences in experimental conditions, such as ambient temperature and feeding manner, physiological status and animal species.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown by Sevi et al (2002) that in heat stressed ewes, the FA profile of milk fat had higher proportions of SFA and lower proportions of oleic acid and PUFA. Moreover, Perry et al (1998) observed an increase in C16:0 and C18:0 and a decrease in C18:1 of subcutaneous fat when steers were exposed to higher ambient temperatures.…”
Section: Discussionmentioning
confidence: 99%